PRESENCIA DE ENTEROPARÁSITOS EN LECHUGA(Lactuca sativa) EN ESTABLECIMIENTOS DE CONSUMO PÚBLICO DE ALIMENTOS EN EL CERCADO DE LIMA - Tananta V., Iris (2004)
Tananta VI, Chávez VA, Casas AE, Suárez AF, Serrano ME. Presence of enteroparasites (Lactuca sativa) in restaurants of Lima downtown. Rev acad. peru cienc vet 2003; 3(1): 31-36. Parasitic diseases are one of the most serious problems in Public Health among the food borne diseases, mainly due to the high morbidity. Enteroparasitic diseases, especially those related to protozoa have a high prevalence in Peru, mostly affecting children and immunosuppressed people through water and food contaminated with infective larvi forms. This purpose of this study was to determine the degree of enteroparasite contamination in raw vegetables that are served in Lima downtown restaurants. A total of 105 lettuce (Lactuca sativa) samples from restaurants specialized in local food, marinated fish (“ceviche”), and roasted chicken were collected. Samples were processed using the sedimentation method and direct observation, plus the modified Ziehl Neelsen method. The level of contamination was 12,4 ± 6,3% (Giardia sp.: 1,9%; Isospora sp.: 3,8%; Cryptosporidium parvum: 6,7%). It is recommended the continuous monitoring of restaurants by official authorities of the Ministry of Health and local municipalities.